Seed yield and agronomic traits of rainfed beans in early generations. - Rosales Serna, R. (2016)
In the bean breeding program of the semiarid region of Mexico, the selection for seed yield is delayed to late generations. The present study was conducted to measure the level of heterosis, heterobeltiosis and inbreeding depression upon several agronomic traits in segregating populations of rainfed beans. Four populations derived from black seeded parents in the F2 and F3 generations, and seven derived from colored beans in the F3 and F4 generations were sown under rainfed conditions. Parents were also included in the trial. Among the black seeded populations, the one derived from the cross BA T 76 X Negro Qro. showed, in both generations, the highest values for seed yield, total dry matter and heterosis, as well as the highest heterobeltiosis value in the F3 generation. In the colored group, the population derived from the cross 102-M X Bayo Victoria showed the highest values for seed yield and heterosis in both generations, and was the only one that showed heterobeltiosis in both generations. The populations that showed high seed yield and heterosis in the first generation, retained these characteristics in the latter one and were derived from the best parents. The results indicate that in dry beans it is possible to predict the best crosses and to identify the high yielding populations in early generations.